The relationship between eye movement and vision develops before birth - Schöpf, Veronika; Schlegl, Thomas; Jakab, Andras; Kasprian, Gregor; Woitek, Ramona; Prayer, Daniela; Langs, Georg (Frontiers in Human Neuroscience, 2014)
While the visuomotor system is known to develop rapidly after birth, studies have observed spontaneous activity in vertebrates in visually excitable cortical areas already before extrinsic stimuli are present. Resting state networks and fetal eye movements were observed independently in utero, but no functional brain activity coupled with visual stimuli could be detected using fetal fMRI. This study closes this gap and links in utero eye movement with corresponding functional networks. BOLD resting-state fMRI data were acquired from seven singleton fetuses between gestational weeks 30 – 36 with normal brain development. During the scan time, fetal eye movements were detected and tracked in the functional MRI data. We show that already in utero spontaneous fetal eye movements are linked to simultaneous networks in visual- and frontal cerebral areas. In our small but in terms of gestational age homogenous sample, evidence across the population suggests that the preparation of the human visuomotor system links visual and motor areas already prior to birth.